Probiotics in Experimental Ulcerative Colitis: Mast Cell Density and Neuronal Hypertrophy - Hizay, Arzu; Keleş-Çelik, Nigar; Acar, Nuray; Çomak-Göçer, Emine Mine; Şekerci, Rahime; Öz, Nuriye; Golal, Ezgi; Elpek, Gülsüm Özlem (Turkish Journal of Gastroenterology, 2022)
Background: Probiotics such as Lactobacillus and Bifidobacterium are among the supportive treatment methods to achieve effective results in ulcerative colitis. This study was established to investigate the effect of probiotics in experimental ulcerative colitis and to detect changes in mast cell and neuronal structures in this treatment method. Methods: A total of 48 adult male rats were used to study the effects of probiotics on ulcerative colitis. The animals were divided into 6 groups as control, experimental colitis, and four probiotic protective groups. Three different bacterial strains were administered to the protective groups individually and in combination by gavage. PGP 9.5 antibody and mast cell tryptase were used for the detection of neuronal structures and mast cells. The number of Schwann cells and ganglia, size measurements of ganglia, and density of mast cells were evaluated. Results: Compared to the control, an increase in the number of mast cells was detected in all groups. Especially the increase in the num- ber of mast cells was found to be statistically significant in combined probiotic administration. In the detection of neuronal structures, a significant increase in the number of Schwann cells and ganglia was detected in groups where probiotics were administered combined and individually. Conclusion: These results suggest that probiotics may play a role in the supporting effect of increasing the number of mast cells and neuronal structures, protecting the intestinal wall. We think that more specific and detailed studies should be conducted to evaluate the protective/therapeutic effect of probiotics in future studies. Cite this article as: Hizay A, Keleş-Çelik N, Acar N, et al. Probiotics in experimental ulcerative colitis: Mast cell density and neuronal hypertrophy. Turk J Gastroenterol. 2022;33(10):822-830.